Fan Ye's Book of Later Han (Houhanshu) military history and ethnicity - Fan, Ye 398-445 (Brill, 2023)
"The Book of Later Han (Houhanshu) by Fan Ye (398-445) is enormously important as China's most complete work on Eastern Han history in biographical form. For the first time in any Western language, the author introduces Fan Ye's magnificent writings in lively translation with rich annotation and informative and insightful commentary. This first volume covers its early military history and highlights the lives and achievements of the twenty-eight generals who helped Emperor Guangwu unify China and establish the Eastern Han dynasty. Also included are images of these twenty-eight founding fathers, maps, and information related to early Eastern Han systems"--
Keywords: Hou Han shu; Geschichte 25-220; Englisch; Übersetzung; Östliche Handynastie; China; China / History / Han dynasty, 202 B.C.-220 A.D.; China / History, Military / 221 B.C.-960 A.D.; Chine / Histoire / 202 av. J.-C.-220 (Dynastie des Han); Chine / Histoire militaire / 221 av. J.-C.-960; Han Dynasty (China); 221 B.C.-960 A.D.; History; Military history; Quelle